Rapid screening for malignancy in organ donors: 15‐year experience with the Verona "Alert" protocol and review of the literature. Issue 9 (25th July 2017) - Eccher, Albino; Cima, Luca; Ciangherotti, Andrea; Montin, Umberto; Violi, Paola; Carraro, Amedeo; Tedeschi, Umberto; Nacchia, Francesco; Fior, Francesca; Rostand, Momo; Boschiero, Luigino; D'Errico, Antonietta; et al.
Abstract: Background: Prevention of transmission of malignancy from donors to recipients is an aim of donor assessment. We report the most stringent interpretation of the Italian National Guidelines. Methods: A two‐step ALERT process was used: ALERT1 consisting of clinical, radiological, and laboratory tests; ALERT2, consisting of intraoperative assessment in suspicious lesions. Results: Four hundred of 506 potential deceased donors entered the ALERT system. Forty‐one of 400 (10%) donors were excluded due to unacceptable risk of transmission. Of the remaining 359 193 required histopathology, which excluded malignancy or determined acceptable risk in 161/193 (83%). Thirty‐five malignancies were identified: 19 (54%) at ALERT1, four (11%) at ALERT2, nine (26%) picked up at ALERT1 and confirmed by ALERT2. Three (9%) were missed by ALERT and diagnosed at postmortem examination. Prostate (n=12%, 34%) and renal cell (n=7%, 20%) were the most frequent carcinomas. The majority (92%) of prostate adenocarcinomas were of low risk and donation proceeded compared to 43% of renal carcinomas. Four renal carcinomas, two breast carcinomas, and a single case of nine different malignancies excluded donation. Positive ALERT donors had statistically more malignant reports than negative ALERT donors ( P =<.05). Conclusion: Histopathology is an essential component of the multidisciplinary assessment of donors.